2003
DOI: 10.1063/1.1597494
|View full text |Cite
|
Sign up to set email alerts
|

Onset of collisionless magnetic reconnection in thin current sheets: Three-dimensional particle simulations

Abstract: Three-dimensional (3D) particle-in-cell simulations of collisionless magnetic reconnection are presented. The initial equilibrium is a double Harris-sheet equilibrium and periodic boundary conditions are assumed in all three directions. No magnetic seed island is imposed initially, and no flow conditions are imposed. The current sheet width is assumed to be one ion inertial length calculated with the density in the center of the current sheet. The ion to electron mass ratio is mi/me=150, which suppresses the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 21 publications
7
97
2
Order By: Relevance
“…The ion flow is also modified, but to a much smaller degree due to the large inertia. The essential physics of this electron acceleration process is very different from recent results [14,15] in which an inductive electric field plays the dominant role while the electrostatic field is negligible [14]. In addition, these low mass ratio simulations do not observe the strong current bifurcation.…”
contrasting
confidence: 43%
See 1 more Smart Citation
“…The ion flow is also modified, but to a much smaller degree due to the large inertia. The essential physics of this electron acceleration process is very different from recent results [14,15] in which an inductive electric field plays the dominant role while the electrostatic field is negligible [14]. In addition, these low mass ratio simulations do not observe the strong current bifurcation.…”
contrasting
confidence: 43%
“…However, new results from both theory and simulation are beginning to challenge this conclusion. In a number of simulations, a strong enhancement of the central current density associated with the LHDI is observed [12 -16] and it has been suggested this effect gives rise to the rapid onset of reconnection [14,15]. Most of these simulations were performed with artificial ion to electron mass ratios m i =m e 100-400 and very thin layers i =L 1:7-2:2, where L is the half thickness of the layer.…”
mentioning
confidence: 99%
“…For the thinnest case, i / L = 1.828, the LHDI causes a peaking of the current profile. This effect has been documented in previous works [12][13][14][16][17][18]28 and the alteration is primary due to electron acceleration: the ion and electron density modifications are weaker. 12,13,16 Within a fluid model, current peaking due to LHDI was also predicted in Ref.…”
Section: Nonlinear Evolution Of the Lhdimentioning
confidence: 68%
“…4 Recently, the effects of the LHDI have been revisited. [12][13][14][15][16][17][18] In the present paper, it is shown that the LHDI may play an important role in the onset of magnetic reconnection, but through a mechanism very different in nature than anomalous resistivity. Although the LHDI is a microscopic instability, it is also responsible for macroscopic changes in the current sheet.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although some questions remain in turbulent plasmas, most recent investigations have found that, in the central magnetic reconnection region, the relevant additional term is provided by the thermal inertia. [2][3][4][5][6][7][8][9][10] The physics behind this is associated with the transient nature of particle orbits in the reconnection region. Pre-acceleration particles are continuously transported into the reconnection region, whereas accelerated particles tend to leave.…”
Section: Introductionmentioning
confidence: 99%